The relationship between facebook usage and self-disclosure among army personnel / Adnan Ajis - Adnan , Ajis (2021)
The popularity of Facebook has attracted billions of users, including members of the Armed Forces, to utilise this social media. This phenomenon has increased the sharing of personal information online, potentially exploiting various parties for their benefits. This study aims to identify the factors that influence users to disclose personal information on Facebook. Therefore, two research questions were developed to examine the issues of Facebook self-disclosure among army personnel. Firstly, what is the level of Facebook self-disclosure among Army personnel? Secondly, what are the factors that affect Facebook self-disclosure among Army personnel? Accordingly, this study emphasised users' gratification as motives that influence individuals to disclose and share social media information. This study applied a quantitative approach to identify the affecting of Facebook self-disclosure factors among Malaysian Army users. A total of 1513 Malaysian Army Facebook users were involved in this study. The research model was developed through a previous literature review. Consequently, the quantitative data analysis utilised the Structural Equation Modelling - Partial Least Squares Technique (SmartPLS 3.0) to test the validity and relationships between the variables hypothesised in the research model. The PLS structural model results had provided statistical evidence supporting the relationship between Facebook motives and self-disclosure. The study found that information sharing, social interaction, entertainment and self-expression were positively significant to self-disclosure. This research provided several contributions and offered valuable insights on the Facebook self-disclosure among the Malaysian Army. In practical contribution, it gave a better understanding of human behaviour on Facebook usage to overcome the information security issues caused by self-disclosure activities. Whereas in the theoretical sense, it impacted the body of knowledge in several areas, as such Facebook self-disclosure model, uses and gratifications theory, research methodology, quantitative methods and measurement model. Furthermore, the methodological and practical implications were also discussed, and several potential avenues for future research had been identified and proposed accordingly. In summary, this research provided a more comprehensive global picture of Facebook self-disclosure that led to information security issues.